Investigation of plasticity mechanisms in shock-compressed matter via femtosecond x-ray diffraction - Sliwa, M (2019)
The microstructural evolution of dynamically-compressed metals has been an area of active research for decades. This work uses a method of x-ray diffraction from highly-textured tantalum foils in order to identify plastic mechanisms mediating plastic deformations in shock-compressed tantalum. The obtained data provides evidence of shock-induced lattice rotations as well as the first in situ observation of shock-induced twinning. The study extends into an analysis of data capturing material as it returns to ambient conditions. It outlines a method of extracting time and depth-dependent strain profiles within the Ta target as the release wave travels back into the bulk of the sample. In agreement with molecular dynamics simulations, the lattice rotation and the twins that are formed under shock compression are observed to be almost fully eliminated by the rarefaction process. Finally, the investigation of thermal effects present during shock release is performed. Immediately after release, the temperatures of the samples are inferred from changes in the atomic lattice spacing which are the result of thermal expansion. It is found that simulations and experimental data suggest significantly larger temperatures of a material after its return to ambient condition than predicted by the theory of isentropic release.